A FORMAÇÃO CONTINUADA NO PACTO NACIONAL PELA ALFABETIZAÇÃO NA IDADE CERTA – PNAIC – E A PRÁTICA DOS PROFESSORES ALFABETIZADORES NO MUNICÍPIO DE RIO AZUL – PR - PIRES, ANDRÉA DE PAULA (2016)
This research presents an analysis of the continuing education policy of Pacto Nacional pela Alfabetização na Idade Certa – PNAIC, implemented by the Federal Government since 2012. The investigated policy intends to the continuing education of literacy teachers. The objective of the research is to analyze the continuing formation of PNAIC in practice of the literacy teachers of the municipal school system of Rio Azul – PR, as well as to explain the main topics of the research, the concepts of continuing education that are present in the educational policy and to investigate how improvement in practice the continuing education has provided opportunities to the teachers. It was used as a theoretical-methodological reference the policy cycle approach (Bowe; Ball; Gold,1992), Ball (1990, 1994, 1997, 2001, 2002, 2006, 2008, 2011), also including Mainardes; Marcondes (2009), Mainardes (2006, 2007, 2009), focusing on the analysis of the first three contexts: influence context, text production context and practice context. There were also contributions from authors who base conceptions of: Public Policy: Azevedo (2004, 2011, 2014).Literacy: Soares (2003, 2004, 2014); Freire (1983, 2000, 2005), Ferreiro (1993, 2002), Mortatti (2000, 2004, 2010); Continuing Education: Nóvoa (1991, 1992, 1995, 2009), Imbernón (2009, 2010, 2011), Tardif (2012, 2013) and Candau (2008). The performed research concerned the following data collection strategies; 1) bibliographic research; 2) documentary research; 3) empirical research carried out in the city of Rio Azul - PR with two PNAIC study guides and nine literacy teachers who joined in the continuing education of this policy in the years 2013 and 2014. The view analysis of the study guides and the participating literacy teachers in this work paper allowed to infer that the PNAIC as an innovating and necessary action, but not sufficient for an effective push of the education quality. Therefore, it is argued that for an improvement of quality, it demands a succession of other practices, which go beyond the continuing teacher education, such as: a greater appreciation of the teaching profession, better working conditions, improved school infrastructure, encouragement for development of educational proposals and policies with the participation of teachers, as well as, strengthening educational policies aimed at inclusion. However, continuing teacher education policies need to be articulated with other policies, since the learning and improving problem of the public education quality demands a plurality of actions and interventions that go beyond continuing teacher education.